Solimano, l’arte pagana del comando nella 'Gerusalemme liberata' di Torquato Tasso e la 'Historia belli sacri' di Guglielmo di Tiro - Verbaere, Lies (Incontri. Rivista europea di studi italiani, 2020)
Solimano, the pagan art of leadership in Torquato Tasso’s Gerusalemme liberata and William of Tyre’s Historia belli sacriThe present article discusses Torquato Tasso’s (1544-1595) representation of leadership in the Gerusalemme liberata (1581), which recounts the Christian army’s conquest of Jerusalem during the First Crusade (1095-1099). More specifically, this article focuses on pagan leadership, taking into account the Renaissance idea about the perfect prince and captain on the one hand, as Cinquecento intellectuals were attempting to shape the ideal Christian captain, and on the other hand Tasso’s use of historiography. Through a comparison with William of Tyre’s (ca. 1130-1186) Historia belli sacri (1170-1184), one of Tasso’s principal sources on the First Crusade, this article shows how Tasso manipulates the Historia in creating characters of leaders. From this new thematic angle, the article confirms the analysis of the complex character of Solimano, Sultan of Nicea, considering a particular aspect, i.e. his leadership. The article aims to demonstrate that Tasso distinguishes between ‘oriental tyrants’ and Solimano, adding heroic traits to the latter and drawing distinct parallels between the ‘Soldano’ and Goffredo.